High-resolution characterization of the forbidden Si 200 and Si 222 reflections - Zaumseil, Peter (Journal of applied crystallography, 2015)
The occurrence of the basis-forbidden Si 200 and Si 222 reflections in specular X-ray diffraction ω-2Θ scans is investigated in detail as a function of the in-plane sample orientation Φ. This is done for two different diffractometer types with low and high angular divergence perpendicular to the diffraction plane. It is shown that the reflections appear for well defined conditions as a result of multiple diffraction, and not only do the obtained peaks vary in intensity but additional features like shoulders or even subpeaks may occur within a 2Θ range of about ±2.5°. This has important consequences for the detection and verification of layer peaks in the corresponding angular range